2008
DOI: 10.1136/gut.2007.134221
|View full text |Cite
|
Sign up to set email alerts
|

P2X receptor-mediated visceral hyperalgesia in a rat model of chronic visceral hypersensitivity

Abstract: These data suggest that the large enhancement of P2XR expression and function may contribute to the maintenance of visceral hypersensitivity, thus identifying a specific neurobiological target for the treatment of chronic visceral hyperalgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
138
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(150 citation statements)
references
References 45 publications
12
138
0
Order By: Relevance
“…19,20 The rats were anesthetized with mild sedation (1% Brevital, 25 mg/kg intraperitoneal [i.p.]). A balloon made from a surgical glove finger was attached to tygon tubing.…”
Section: Behavioral Test For Nocifensive Responses To Colorectal Distmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 The rats were anesthetized with mild sedation (1% Brevital, 25 mg/kg intraperitoneal [i.p.]). A balloon made from a surgical glove finger was attached to tygon tubing.…”
Section: Behavioral Test For Nocifensive Responses To Colorectal Distmentioning
confidence: 99%
“…As described previously, 20,22 DRG neurons innervating the colon were labeled by injection of fluorescent dye DiI (Invitrogen, New York, NY, USA) into the colon wall. Rats were anesthetized with chloral hydrate (0.36 g/kg i.p.…”
Section: Cell Retrograde Labelingmentioning
confidence: 99%
“…As a neurotransmitter, ATP plays an important role in regulating the transduction of the visceral pain signal by binding to P2X receptors [15,16], and ATP participates in the regulation of intestinal movement and gastrointestinal secretion. P2X receptors are widely distributed in the body, and they play an important role in the formation, transduction, and regulation of neuropathic pain, inflammatory pain, and visceral pain [17][18][19][20]. Many studies have shown that purinergic (P2X) receptors are involved in pain signal transmission, in which the P2X 3 and P2X 2/3 receptors are the main subtypes [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies only documented upregulation of the P2X3 purinoceptor in DRG neurons in different neuropathic pain models [4,5,7], and peripheral P2X3 sensitization contributed to neuropathic pain, suggesting the pathology of P2X3 purinoceptors in peripheral tissues linked to neuropathic pain [17].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies documented upregulation of the P2X3 purinoceptor in peripheral neuropathic pain, for example in mechanical injury-induced focal neuropathy [4], in a chronic visceral pain model [5,6], and in chemotherapy-induced neuropathy [7]. The roles of P2X3 activation in neuropathic pain were confirmed by functional blockade [8][9][10] and by administering exogenous ATP, which evokes pain behaviors [11,12].…”
Section: Introductionmentioning
confidence: 83%